2017
DOI: 10.24251/hicss.2017.490
|View full text |Cite
|
Sign up to set email alerts
|

So Much Promise, So Little Use: What is Stopping Home End-Users from Using Password Manager Applications?

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Alkaldi and Renaud [1] studied the reasons that can lead to adoption or rejection of smartphone password managers. In another study, Aurigemma et al [4] argued that the lack of password manager usage might be due to lack of trust, perceived…”
Section: B the Use Of Password Managersmentioning
confidence: 99%
“…Alkaldi and Renaud [1] studied the reasons that can lead to adoption or rejection of smartphone password managers. In another study, Aurigemma et al [4] argued that the lack of password manager usage might be due to lack of trust, perceived…”
Section: B the Use Of Password Managersmentioning
confidence: 99%
“…A previous study found that people are generally unaware of password managers [8], so an awareness video was included in the intervention. We used the same awareness video clip that was used by Aurigemma et al's study [45]. This video provides an overview of password managers, and the reason for using them, and details the attractive features of such tools, such as its usefulness and effectiveness.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, Fagan et al found that users of password managers have higher computer proficiency and better experience of computer security than non-users; they found that convenience, security and usefulness are the main reasons for using password managers by users, while non-users noted security and usability as the main reasons for not using them [9]. Similarly, it was reported that a lack of immediacy and time are the most common reasons for not downloading and using password management applications [32]. Gao et al applied an ecological theory in a study on passwords which found that participants expressed fewer concerns about using password managers, such as the risk of password manager databases being hacked or accidental password loss [21].…”
Section: Related Workmentioning
confidence: 99%